Peculiarities of Termination of Employment Relations with an Employer’s Representative at the Initiative of the Employer - Haykyants, Armen; Karapetyan, Mane (Bulletin of Yerevan University C: Jurisprudence, 2022)
The topic of the Article is dedicated to the institute of termination of employment relations with the employer’s representative. The special role of the employer’s representative, as a subject of labor law, characterizes the uniqueness of his/her status, as a result of which both general and special regulations of the labor legislation are applied in relations with him/her. In this context, it is obvious that unlike other employees of the organization, the employment legal status of the employer’s representative is dualistic, since, on the one hand, he/she enters into employment contracts on behalf of the employer or applies disciplinary measures as an example, and on the other hand, he/she performs work and receives a salary. Within the scope of this Article, the experience of foreign countries was studied, doctrinal approaches were referred to, and the existing RA judicial practice on the issue was presented alongside with the practice of the Republic of Armenia around the problem. Having completed the work, the authors proposed to legislate also the specifics of termination of employment relations with an employer’s representative, establishing the right of organizations to terminate an employment contract concluded with an employer’s representative without any grounds and at any time.